The Big Four of Influencer Marketing - A Typology of Influencers - Jana Gross; Florian von Wangenheim (Marketing Review St.Gallen, 2018)
Selecting the right type of influencers for an influencer campaign is a challenging task. This article introduces a typology for influencers presenting four distinct types: Snoopers, Informers, Entertainers, and Infotainers. Temporal dynamics and influencer type transitions based on social presence and domain breadth are shown to provide a guideline for companies to successfully scout influencers.
Keywords: 650